Contemporary insights into the pathogenesis and treatment of chronic myeloproliferative neoplasms. Issue 7 (2nd July 2016) - Mughal, Tariq I.; Abdel-Wahab, Omar; Rampal, Raajit; Mesa, Ruben; Koschmieder, Steffen; Levine, Ross; Hehlmann, Rüdiger; Saglio, Giuseppe; Barbui, Tiziano; Van Etten, Richard A.
Abstract: This review is based on the deliberations at the 5th John Goldman Colloquium held in Estoril on 2nd October 2015 and the 9th post-ASH International Workshop on chronic myeloid leukemia (CML) and BCR-ABL1 -negative myeloproliferative neoplasms (MPN) which took place on the 10th–11th December 2014, immediately following the 56th American Society of Hematology Annual Meeting. It has been updated since and summarizes the most recent advances in the biology and therapy of these diseases, in particular updates of genetics of MPN, novel insights from mouse MPN models, targeting CML stem cells and its niche; clinical advances include updates on JAK2 inhibitors and other therapeutic approaches to BCR-ABL1 -negative MPNs, the use of alpha interferons, updates on tyrosine kinase inhibitors (TKI) randomized trials in CML, TKI cessation studies, and optimal monitoring strategies.